Oncologic outcomes of supratracheal laryngectomy: Critical analysis. Issue 10 (19th July 2014) - Rizzotto, Giuseppe; Crosetti, Erika; Lucioni, Marco; Bertolin, Andy; Monticone, Valentina; Sprio, Andrea Elio; Berta, Giovanni Nicolao; Succo, Giovanni
Abstract: Background: Laryngeal cancer management should pursue function‐sparing therapeutic options. Even though demolitive surgery provides better control of disease at intermediate to advanced stages when compared to chemoradiotherapy, it does not preserve laryngeal function. Supratracheal partial laryngectomy has been described as a function‐sparing surgical technique for laryngeal cancer with subglottic extension. Methods: In this retrospective study, we analyzed the clinical outcomes of 115 patients who underwent supratracheal partial laryngectomy. Results: At 5 years, overall survival (OS), disease‐free survival (DFS), and locoregional control rates were 78.9%, 68.5%, and 69.6%, respectively; DFS and locoregional control prevalences were greatly affected by pT4a classification (49.0% and 51.4%, respectively); and laryngeal function preservation was maintained in 78.3% of patients despite being affected by pT4a classification (59.3%) and age ≥65 (64.6%). Conclusion: For cases with glottic tumors and with subglottic extension, the choice of supratracheal partial laryngectomy versus chemoradiotherapy can be considered to be effective in terms of prognostic and functional results. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1417–1424, 2015